1988
DOI: 10.1093/nar/16.5.1931
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent chemical and enzymatic probing of the tRNA-like structure of TYMV RNA

Abstract: In this paper we report on the thermal unfolding of the tRNA-like structure present at the 3' end of turnip yellow mosaic virus (TYMV) RNA. Diethyl pyrocarbonate (DEP), sodium bisulphite, nuclease S1 and ribonuclease T1 were used as structure probes at a broad range of temperatures. In this way most of the nucleotides present in the tRNA-like moiety were analysed. The melting behaviour of both secondary and tertiary interactions could be followed on the basis of the temperature dependent accessibility of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…It has been shown that several tymoviral genomic RNAs can be aminoacylated with valine (Rietveld et al, 1982), however the fact that ELV could not be acylated led van Belkum et al (1987) to suggest that ELV might lack a tRNA-like structure, and this agrees with our results. It is uncertain how essential are the 3'-terminal tRNA-like structures of tymoviruses.…”
Section: The Terminal Untranslated Regions Of the Genomessupporting
confidence: 91%
See 1 more Smart Citation
“…It has been shown that several tymoviral genomic RNAs can be aminoacylated with valine (Rietveld et al, 1982), however the fact that ELV could not be acylated led van Belkum et al (1987) to suggest that ELV might lack a tRNA-like structure, and this agrees with our results. It is uncertain how essential are the 3'-terminal tRNA-like structures of tymoviruses.…”
Section: The Terminal Untranslated Regions Of the Genomessupporting
confidence: 91%
“…The sequence of each clone was determined, in both orientations. Their 5' portions were homologous, and they terminated in -C or -C(A) like other tymoviruses (van Belkum et al, 1987). It is unlikely that the ELV genome has a longer poly(A) tail as the primer dT8G failed to assist transcription unless the genomic RNA had been polyadenylated.…”
Section: Nucleotide Sequence Of the El V Genomementioning
confidence: 98%
“…S nuclease digestions were carried out with 2 units (0°C), 1 unit (37°C) and 0.2 unit (55°C) for 60, 30 and 8 minutes, respectively (for more experimental details see also [20]). Digestion was stopped by the addition of 100 Zl ethanol, followed by centrifugation.…”
Section: Chemical Modification Sequencing and Enzymatic Digestionmentioning
confidence: 99%
“…3'-Terminally labeled transcripts were analysed by diethyl pyrocarbonate and sodium bisulphite modification and RNase T I digestion at various temperatures as described for the 112-nucleotide fragment [15]. were identified and treated as described for the 112-nucleotide fragment .…”
Section: Isola Tion 9 F Transcriptsmentioning
confidence: 99%
“…It is clear that pseudoknots are important elements in RNA structure and functioning. The pseudoknot that has been investigated most thoroughly using both biochemical [3,4,14,15] and computer graphics [16] methods, is the one present in the aminoacyl acceptor arm of the tRNA-like structure of turnip yellow mosaic virus RNA. However, the current model, which accomodates most of the data available, needs biophysical verification.…”
mentioning
confidence: 99%